When Wilderness Was King : A Tale of the Illinois Country - Parrish, Randall, 1858-1923 (Salt Lake City, UT : Project Gutenberg, 2006)
"When Wilderness Was King" by Randall Parrish is a historical novel written in the early 20th century. The narrative takes place in the American frontier, specifically along the upper Maumee River, during a time of tension between settlers and Native American tribes. The story revolves around John Wayland, a young man who must navigate the dangers of this rugged wilderness, compelled by a duty to bring back an orphaned girl after the death of her father, a friend of his family. The opening of the novel introduces us to John Wayland's peaceful life at home in the backwoods, and it foreshadows a drastic change as he receives a letter urging his father to take in the surviving daughter of an old comrade. As John contemplates this new duty, we meet Ol' Tom Burns, a grizzled traveler who delivers the fateful message, marking the beginning of John's journey into the unknown. The narrative blends themes of adventure, duty, and the elements of wilderness survival as John prepares to face the perils that lie ahead, all while wrestling with his own youthful ambitions and fears. (This is an automatically generated summary.)
Release date is 2006-03-01
E-text prepared by Al Haines
Keywords: Illinois -- Fiction